Crimes against humanity in the 21st century: law, practice, and threats to international peace and security - Dubler, Robert (Brill Nijhoff, 2018)
The origins of the concept of crimes against humanity -- The Nuremberg precedent -- From Nuremberg to the Hague -- 1993-1998 : the modern definition of crimes against humanity -- The law of the international and internationalised tribunals -- The law of the International Criminal Court -- State practice after the Rome Conference of 1998 -- Crimes against humanity and threats to international peace and security -- Crimes against humanity under customary international law and the ICC : the Chapeau elements -- Crimes against humanity under customary international law and the ICC : the underlying crimes -- Prosecuting crimes against humanity in domestic courts